Unusual manifestation of systemic lupus erythematosus - Dhiman, Himanshu; Sood, Vivek; Rana, Baldev Singh; Sharma, Tarun (Indian Journal of Case Reports, 2020)
The systemic lupus erythematosus (SLE) is a multisystem disease, and involvement of the gastrointestinal system is seen in about half of SLE patients. As a rare complication of SLE, acute pancreatitis presents as generalized flare-ups inpatients previously diagnosed with SLE. Lupus pancreatitis is more common in females and the third decade of life with an incidence ranging from 0.7% to 4%. Here, we report a rare case of acute pancreatitis as the initial presentation with later patient was diagnosed as a case of SLE, thus forming an unusual presentation of SLE.